2020
DOI: 10.1038/s41409-020-01092-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of infection and infectious-related mortality in patients receiving post-transplant high dose cyclophosphamide as graft-versus-host-disease prophylaxis: impact of HLA donor matching

Abstract: Post-transplant cyclophosphamide (PTCy) has become a promising option after allo-SCT, but infections may be more common than in traditional protocols. We herein report 117 consecutive adults who received PTCy-based alloSCT in our hospital: HaploSCT (34%), MRD (19%), and VUD (47%), respectively. The 18-month incidence of severe bacterial, viral, and IFI was 56%, 69%, and 8.7%, without differences between donor type, except for CMV infection and viral hemorrhagic cystitis, which had a higher incidence in the hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
(69 reference statements)
4
29
2
Order By: Relevance
“…Changes in clinical practice during this study period included the decreased use of ATG and T-cell depleted graft and increased use of post-transplant cyclophosphamide for GVHD prophylaxis. Post-transplant cyclophosphamide has been shown to increase the incidence of CMV infection in CMV-seropositive recipients and was more commonly used in our letermovir group [ 23 , 24 , 25 ]. ATG has also been shown to be associated with increased risk of CMV reactivation, but it is important to consider that many of these trials including ATG were conducted before letermovir was used to prevent CMV infection [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in clinical practice during this study period included the decreased use of ATG and T-cell depleted graft and increased use of post-transplant cyclophosphamide for GVHD prophylaxis. Post-transplant cyclophosphamide has been shown to increase the incidence of CMV infection in CMV-seropositive recipients and was more commonly used in our letermovir group [ 23 , 24 , 25 ]. ATG has also been shown to be associated with increased risk of CMV reactivation, but it is important to consider that many of these trials including ATG were conducted before letermovir was used to prevent CMV infection [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include an alteration of the Treg-Tcon ratio, delayed T cell recovery kinetics and selective depletion of alloreactive T cell clones 26 . Infections following PT-CY are common, albeit, non-lethal 27 . ATG when compared with PT-CY retrospectively yields equivalent outcomes in MUD recipients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CMV DNA peak load was remarkably higher in haploSCT recipients, but the mortality by days 180 and 365 did not differ among comparison groups (55). Garcıá-Cadenas Irene et al studied the impact of HLA donor matching on infection in patients receiving PTCy-based alloSCT (59). They found that haploSCT recipients had a higher incidence of CMV infection/ reactivation at 18 months than other transplant modalities [(61% (95% CI: 41-74%) vs. 44% (95% CI: 31-54%)], whereas lethal infections were uncommon across all these groups.…”
Section: Ptcy-haplosctmentioning
confidence: 99%